Forensic Monitoring Project Report: Rogatica Exhumations II State Commission on Missing Persons - Physicians for Human Rights
Forensic report on individual and mass grave exhumations in Bosnia and Hercegovina created during the Forensic Assistance Project (FAP). The report was authored by: Connor, Melissa The State Commission on Missing Persons (Bosniak) exhumed 14 individuals from sites in the Rogatica area between 4-8 October 1998 and 29 individuals between 4-11 November 1998. Ther recovered remains were from fighting that took place in 1992 in and around Rogatica. Place of Exhumation: Rogatica Exhumation Site: Brčigovo, Izgumanje, Kukavice, Seljani, Bijelogorci, Granćanica, Surovi, Kujundžijevici, Rogatica, Rudine, Golubovići, Rasadnik, Lunj, Kovanj Date of Exhumation: 4-8 October; 4-11 November 1998 Minimum Number of Exhumed Individuals: 043